1984
DOI: 10.1111/j.1464-410x.1984.tb06128.x
|View full text |Cite
|
Sign up to set email alerts
|

Urological Problems Following Treatment of Carcinoma of the Cervix

Abstract: One thousand one hundred and sixty-one cases of carcinoma of the cervix presenting over a 20-year period to 1982 were considered: 326 (28%) of these women developed urological problems, of whom 82 (7%) had major complications. Fistula formation occurred in 46 cases (4%), and was associated with active malignant disease in 33. Significant progressive ureteric obstruction occurred in 15 patients, 11 of whom had active malignancy. Overall, 35 (43%) of 82 patients with major urological problems had no evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Unfortunately, treatment of severe late complications often involve multiple surgical repairs such as augmentation cystoplasty with disappointing results [8]. Jones et al reported the prevalence of severe bladder complications in women treated with radiation therapy as the primary treatment for cervical cancer as 7.1% (81/1161) and with fistula formation 4.0% (46/1161) the most common major bladder complication [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, treatment of severe late complications often involve multiple surgical repairs such as augmentation cystoplasty with disappointing results [8]. Jones et al reported the prevalence of severe bladder complications in women treated with radiation therapy as the primary treatment for cervical cancer as 7.1% (81/1161) and with fistula formation 4.0% (46/1161) the most common major bladder complication [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The commonest symptoms were urgency and urge incontinence, experienced by 45%, and frequency in 33%. A retrospective case record study (Jones et al, 1984) found 21% of women had minor urological problems following treatment of cervical carcinoma.…”
mentioning
confidence: 99%
“…Gynecological cancers are common causes for vesicovaginal fistulae and have been reported to occur in 4-6% of patients after previous therapies but may reach up to 50% at advanced stages of the disease [11][12][13] . Repair of such fistulations is randomly successful and indicated in few cases only [14] .…”
Section: Discussionmentioning
confidence: 99%